Increased plasma corticosterone contributes to the development of alcoholic fatty liver in mice - Sun, Xiuhua (American Physiological Society, 2013)
Ethanol ingestion increases endogenous glucocorticoid levels in both humans and rodents. The present study aimed to define a mechanistic link between the increased glucocorticoids and alcoholic fatty liver in mice. Plasma corticosterone levels were not affected in mice on a 2-wk ethanol diet regimen but significantly increased upon 4 wk of ethanol ingestion. Accordingly, hepatic triglyceride levels were not altered after 2 wk of ethanol ingestion but were elevated at 4 wk. Based on the observation that 2 wk of ethanol ingestion did not significantly increase endogenous corticosterone levels, we administered exogenous glucocorticoids along with the 2-wk ethanol treatment to determine whether the elevated glucocorticoid contributes to the development of alcoholic fatty liver. Mice were subjected to ethanol feeding for 2 wk with or without dexamethasone administration. Hepatic triglyceride contents were not affected by either ethanol or dexamethasone alone but were significantly increased by administration of both. Microarray and protein level analyses revealed two distinct changes in hepatic lipid metabolism in mice administered with both ethanol and dexamethasone: accelerated triglyceride synthesis by diacylglycerol O-acyltransferase 2 and suppressed fatty acid β-oxidation by long-chain acyl-CoA synthetase 1, carnitine palmitoyltransferase 1a, and acyl-CoA oxidase 1. A reduction of hepatic peroxisome proliferation activator receptor-α (PPAR-α) was associated with coadministration of ethanol and dexamethasone. These findings suggest that increased glucocorticoid levels may contribute to the development of alcoholic fatty liver, at least partially, through hepatic PPAR-α inactivation.